Inter-firm patent litigation networks: a study of network motif analysis - Kito, Tomomi; Murata, Yuki; Yamanoi, Junichi; Madhavan, Ravi (Frontiers in Physics, 2024)
This paper provides a comprehensive exploration of the competitive dynamics among firms within the realm of intellectual property, specifically focusing on patent litigation relationships from a network science perspective. Despite the extensive research on patents and litigated firms, little attention has been paid to the underlying mechanisms shaping relationship structures. Utilizing longitudinal data on patent infringement lawsuits in the US and the involved firms, we construct a patent litigation network among firms and scrutinize its structural features and tie formation mechanisms. Our findings reveal the significant influence of mechanisms such as homophily, popularity, and activity on network formation, with reciprocity emerging as a pivotal factor. The absence of triadic closure is also observed. These distinct structural patterns persist consistently across various technological fields and timeframes. Furthermore, our analysis delves into the prevalent strategy of prompt countersuits within this network, providing valuable insights into the inter-firm patent litigation strategies. Additionally, our results shed light on the formation mechanisms of networks comprising negative ties.